Study on Step Skewing of Rotor for Permanent Magnet Synchronous Motor - PENG Jun; FU Minli; CHEN Zhichu; HE Siyuan (Kongzhi Yu Xinxi Jishu)
Step skewing of rotor magnets is an efficient method for reducing harmonics and minimizing cogging torque and torque ripple of PMSM. It presents a calculation method of best step skewing angle. Based on finite element analysis, no-load EMF, cogging torque and load torque of a prototype motor with different step numbers are calculated and compared, the principle of choosing step numbers is then obtained. Experimental results verify the correctness of the conclusion.